Ocular hazards of nebulized bronchodilators. - Mulpeter, K. M. (BMJ Group, 1992)
Three cases of pupillary dilatation associated with the development of acute glaucoma, precipitated by the use of nebulized bronchodilators are described. We suggest measures to reduce the risk of this complication.